Ecosystem services in the context of sustainable urban development - Lorek, Agnieszka Anna (Acta Universitatis Lodziensis. Folia Oeconomica, 2016)
Relations between the functioning and benefits of ecosystems to society was considered since the 70s. Conducted research and analysis in this area, as well as the development and refinement of methods for estimating the economic value of ecosystem services are the cause of changes in attitudes among decision-makers and politicians. In recent years, there is an increase of environmental awareness especially in developed countries, which meant that more often, both in scientific papers and documents relating to the development of urban areas, much attention is paid to the ecosystems services. The condition of cities depends on a healthy natural environment, which produces a number of benefits, and healthy ecosystems form the basis for sustainable urban development as a positive impact on human well-being and economic activity. The aim of this article is to present the current state of knowledge on the theoretical aspects of the concept of ecosystem services and their importance for sustainable urban development. Particular attention was paid to the activities undertaken by municipalities in this regard, inter alia, the problem of urban planning in this behavior: both the quantity and quality of green areas and the functioning of aquatic ecosystems and natural water retention.